Exploring the Motivations for Completing Advance Care Directives: A Qualitative Study of Majority/Minority Israeli People Without Dementia - Werner, Perla; Ulitsa, Natalie; AboJabel, Hanan (Frontiers in Psychiatry, 2022)
Background: Completing advance directives has been declared an essential instrument for preserving and respecting the autonomy and preferences for end-of-life care of people living with dementia. However, research deciphering the reasoning behind the decision to complete or not advance directives in the case of dementia remains limited, especially among people pertaining to different majority/minority groups. Objectives: To explore the motivations of people without dementia in Israel to complete or not to complete advance directives and to compare these motivations among the majority veteran Jewish group, the minority Jewish Former Soviet Union immigrant group, and the minority Arab group. Methods: This qualitative study used purposive sampling and focus groups with discussions elicited by a vignette. A total of 42 Israeli people without dementia participated in 6 focus groups: two with veteran Jews (n=14), two with Jewish immigrants from the Former Soviet Union (n=14), and two with Arabs (n=14). The analysis followed recommended steps for thematic content analysis. Results: Four overarching themes were identified: 1) the meaning of dementia-related advance directives, 2) motivations for willingness to complete advance directives, 3) motivations for not being willing to complete advance directives, and 4) ethical dilemmas. Some of the themes were common to all groups, while others were informed by the groups' unique characteristics. Participants displayed a lack of knowledge and misunderstanding about advance directives, and central concepts such as autonomy and competence. Furthermore, stigmatic images of dementia and of the person with the diagnosis were associated to participants' motivations to complete advance directives. Conclusions: There is need to expand comparative research among culturally and socially similar and dissimilar groups within a country as well as between countries in order to better guide public health efforts to increase the rates of advance directives completion. Special attention should be paid to decreasing stigmatic beliefs and understanding unique cultural values and motivations.